2011
DOI: 10.1111/j.1745-3933.2011.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

A merger mystery: no extended radio emission in the merging cluster Abell 2146

Abstract: We present a new 400 ks Chandra X‐ray observation and a Giant Metrewave Radio Telescope (GMRT) radio observation at 325 MHz of the merging galaxy cluster Abell 2146. The Chandra observation reveals detailed structure associated with the major merger event including the Mach M= 2.1 ± 0.2 bow shock located ahead of the dense subcluster core and the first known example of an upstream shock (M= 1.6 ± 0.1). Surprisingly, the deep GMRT observation at 325 MHz does not detect any extended radio emission associated wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 62 publications
0
54
1
Order By: Relevance
“…The existence of massive and merging systems without RHs is well known (Cassano et al 2010Russell et al 2011). If RHs are due to turbulence acceleration of relativistic electrons during cluster mergers they should have a typical lifetime of ∼1 Gyr (see Brunetti et al 2009), which is of the same order of the merger timescale.…”
Section: Radio Halo-cluster Merger Connectionmentioning
confidence: 96%
“…The existence of massive and merging systems without RHs is well known (Cassano et al 2010Russell et al 2011). If RHs are due to turbulence acceleration of relativistic electrons during cluster mergers they should have a typical lifetime of ∼1 Gyr (see Brunetti et al 2009), which is of the same order of the merger timescale.…”
Section: Radio Halo-cluster Merger Connectionmentioning
confidence: 96%
“…If turbulence plays a role in the acceleration and dynamics of relativistic particles radio haloes evolve on a time scale of about 1 Gyr. According to this scenario, the possibility of generating a halo that is sufficiently luminous (detectable by our observations) at the GMRT frequencies depends on the combination of several parameters, including the magnetic field properties of the hosting cluster, the mass of the merging systems, the fraction of the energy of mergers that is drained in turbulence (and its properties), and the stage of the merger Russell et al 2011;Donnert et al 2013;Brunetti & Jones 2014, for a review). Further statistical studies that also consider information on the mass of clusters will be very useful.…”
Section: Cluster Dynamics In Grhs and Egrhsmentioning
confidence: 99%
“…Donnert et al 2013). The non detection of a radio halo for A2146 by Russell et al (2011) might therefore indicate that this cluster fits well into this aged population. However, this is inconsistent with the X-ray observations since the estimated age from the shock fronts puts the cluster at an evolutionary stage of 0.2 − 0.3 Gyr after core passage (see Russell et al 2010White et al 2015), similar to the Bullet cluster, yet the Bullet cluster clearly sits along the correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Using 5.7 hours of observations from the Giant MetreWave Telescope (GMRT) at 325 MHz, Russell et al (2011) found no evidence of extended radio emission in A2146 down to a rms of 250 µJy beam −1 . The only two radio sources detected coincided with A2146-A and a second cluster galaxy to the north (labelled as radio source in Fig.…”
Section: Introductionmentioning
confidence: 99%